(untitled) (Innovative professional education, 2023)
The article considers the concept of «management methods», raises the problem of formation and development of management methods of professional (vocational and technical) education in the conditions of public-private partnerships. The main methods of management, which are the most effective in managing the system of professional (vocational and technical) education in the conditions of public-private partnership, have been studied and characterized. The principles of the formation of a system of management methods in the conditions of partnership interaction have been determined.